Hallucinatory syndromes / Immersion in the image. Classical theories and perspectives (AN-ICON. Studies in Environmental Images [ISSN 2785-7433], 2022)
From the outset, the inventors of 3D, VR/AR and analogue and digital immersion thought of these devices as functional models of our perceptive capacities, serving to expand our sensory knowledge and to support our communications based on multisensory storytelling. How is it that a solid critical tradition then assimilates them to hallucinatory phenomena? The answer lies in marketing techniques that have always associated dreams and illusions with the desire to play with reality. But there is a deeper, epistemic reason.The sources of scientific thought of hallucinations are marked, in the 19th century, by the theory of “sensations without objects.” Perception being distorted, the knowledge it provides is pointless. It is therefore possible to replace the vacant object with our desires to act out subjectively the real. This conviction initiated by Dr. Jean-Étienne Dominique Esquirol has survived to the present day. However, the history of the scientific approach of hallucinations shows another theoretical framework, particularly prolific but curiously forgotten: the theory of reality monitoring and arbitration of sources of information provided from Dr. Henri Ey. We propose to forge on these concepts a critical tool of the current mediadesign.
Keywords: Hallucinatory syndromes; Immersion in the image; Classical theories and perspectives